Prognostic significance of CD3+ tumor-infiltrating lymphocytes in patients with endometrial carcinoma - Čermáková, Petra; Melichar, Bohuslav; Tomšová, Markéta; Zoul, Zdeněk; Kalábová, Hana; Spaček, Jiří; Doležel, Martin (Anticancer research, 2014)
AIM: The aim of the present study was to investigate tumor-infiltrating leukocytes in patients with endometrial carcinoma. PATIENTS AND METHODS: Cluster of differentiation (CD)3(+), CD8(+) and C20(+) tumor-infiltrating lymphocytes (TILs) and CD68(+) tumor-associated macrophages (TAMs) were evaluated retrospectively by immunohistochemistry in tumor specimen from 124 patients with endometrial carcinoma. RESULTS: A significant decrease of CD3(+) TILs and an increase of CD68(+) TAM count was associated with higher tumor stage. In patients with early-stage, high-risk tumors, low intraepithelial CD3(+) TIL counts were associated with significantly inferior survival. In multivariate analysis of patients with early-stage tumors, intraepithelial CD3(+) TIL counts were an independent predictor of survival. CONCLUSION: In patients with endometrial carcinoma a decrease of intraepithelial CD3(+) TIL counts is associated with advanced stage and high risk group. Intraepithelial CD3(+) TIL counts are an independent predictor of survival in patients with early tumors.
Keywords: CD3 Complex; Cell Count; tumor-infiltrating lymphocytes; Lymphocytes, Tumor-Infiltrating; Biomarkers; Neoplasm Grading; prognóza; Neoplasm Staging; antigeny CD3; Aged; senioři; počet buněk; endometrial carcinoma; Endometrial Neoplasms; leukocyty; senioři nad 80 let; tumor-associated macrophages; lidé; ženské pohlaví; stupeň nádoru; Humans; Leukocytes; Aged, 80 and over; Prognosis; Female; tumor infiltrující lymfocyty; lidé středního věku; staging nádorů; nádory endometria; Middle Aged